(3GdeSJWQa ef cd af eSJXQas - (3GdCHTjgj, CHh GdaJM, TgGH GdOjf, eMeO Hf CMeO Hf efUhQ, J(B852(3g`s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdYXje CeG HYO abO QCjJeGYI ef Phj GdgeeeYhG TjFG ef GdCOH hGdMce hHSWhG eLdOGJ aj GdJhGQjNaGSJNQJ Gddg hLeYJ ef eLehYgG gPG GdeLehYhSejJg GdeSJWQa aj cd af eSJXQas
(3BNQgG (B:s
(3hbGd YeQ Hf GdCgje(B: (3dYeQc eG VGbJ HdGO HCgdGgG (B*** (3hdcf CNdGb GdQLGd JVjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 332s
(3eYLe GdeDdajf(B: 3 / 110s
(3cTa GdXfhf(B: 2 / 1674s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs